Extranodal T-Cell Lymphoma of Nasal Cavity - Kumar, Madhu (Springer-Verlag, 2012)
A rare case of primary extranodal lymphoma of nasal cavity is here with reported in a 11 years old female child. Patient presented with space occupying extensive lesion in nasal cavity with destraction of nasal septum and obliteration of paranasal sinuses. After histological examination and routine stain showed a round cell tumor with provisional diagnosis of large cell non-Hodgkin’s lymphoma was made. Immunohistochemical stain were used to further differentiate from other possibilities mimics as carcinoma and round cell tumors. Immunohistochemical stain confirm the diagnosis of extranodal T-cell lymphoma. We report this case for its rarity in paediatric patients.